Pelatihan Optimalisasi Penggunaan Aplikasi Wayground untuk Meningkatkan Kompetensi Asesmen Digital Mahasiswa PGSD Bone - Syamsurijal; Nur Isra Ahmad; Ruhul Kudus; Arlian Fachrul Syahputra; Femmy Angreany (Jurusan Pendidikan Guru Sekolah Dasar Kampus VI Bone, 2026)
Digital transformation in education requires prospective elementary school teachers to develop competencies in designing, implementing, and evaluating technology-based learning assessments. This community service program aimed to improve the digital assessment competence of PGSD Bone students through training on the optimization of the Wayground application. The activity employed a participatory training approach consisting of needs identification, material presentation, application demonstration, independent practice, mentoring, digital assessment product presentation, and evaluation. Evaluation instruments included participant response questionnaires, skill observation sheets, and pretest-posttest assessments. The results indicated that the training improved students’ understanding of digital assessment concepts, skills in creating interactive quizzes, ability to manage digital classes, and competence in analyzing assessment results quickly and objectively. Therefore, this training positively contributed to strengthening the pedagogical competence and digital literacy of PGSD Bone students, particularly in designing creative, engaging, and data-based elementary school learning assessments.